Large Radicular cyst disfiguring the midline face; a case report - Sigdel, Brihaspati; Sah, Kuseshwar; Neupane, Bhima (Birat Journal of Health Sciences, 2022)
A radicular cyst is an inflammatory odontogenic cyst of the jaw commonly found at the apices of the tooth of the anterior maxilla. It develops as a sequel of untreated dental caries with pulp necrosis and periapical infection. Different treatment includes surgical endodontic treatment, extraction of the involving tooth, marsupialization, and enucleation with primary closure followed by rehabilitation. We presented a case of a huge midline radicular cyst of a 52 years lady who presented with increasing size of swelling at the midline of the upper lip region which makes patients ugly for 25 years. It leads to the mass effect at the philtrum of the upper labium at midlines leads to elevation and ugly looking face making her socially embarrassing. Endoscope-assisted complete excision was performed via midline mini visor incision and with no evidence of recurrence found at three-month follow-up.